Analisis Kepuasan Pengguna Aplikasi VSCO di Kota Jambi dengan Menggunakan Metode EUCS - Fitria, Choryn; Benni Purnama; Suyanti Suyanti; Dwi Junita (Prosiding Seminar Nasional Ilmu Teknik, 2025)
The use of the VSCO application continues to face technical issues, including errors during editing, limited feature access, and login problems that affect user satisfaction. This study analyzes user satisfaction with the VSCO application using the End User Computing Satisfaction (EUCS) method. The study involved 385 VSCO users as respondents, with data collected through questionnaires and analyzed using SmartPLS 3.0. In this research, Accuracy variable does not affect user satisfaction, whereas the Content, Format, Ease of Use, and Timeliness variables have a significant effect on user satisfaction. The study shows that content quality, interface design, ease of use, and system timeliness are the main factors influencing user satisfaction with the VSCO application.